THE EFFECT OF BAD DEBTS ON RESIDUAL INCOME AT KAMON COOPERATIVE IN MALAKA DISTRICT - Yanuarius Bria Seran; I Nengah Suastika; I Wayan Lasmawan (Jurnal Ekonomi, 2023)
Credit cooperatives are one of the most developed cooperatives in Indonesia. The business it runs is by collecting funds from members and then the funds provide loans to members. bad debts arise due to the failure of poor credit management and members as debtors do not fulfill their obligations, which will affect the acquisition of Residual Income. Based on the results of this study that the magnitude of the influence of bad debts and the remaining 47% of Sisa Hasil Usaha while the remaining 53% is explained by other variables that are not explained in this study such as member participation in making deposits, loans and income